TANGGUNG JAWAB PIDANA BAGI APARATUR SIPIL NEGARA KARENA TURUT SERTA MELAKUKAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH PEJABAT ATASAN - Sukartha, I Made (Jurnal HUKUM BISNIS, 2025)
This research examines whether civil servants can be prosecuted for participating in corruption crimes committed by their superior officials and what legal measures can be taken to avoid prosecution for participating in corruption crimes committed by their superior officials. This research is a research using descriptive analytical specifications. To clarify this analysis using the approach method: Legislation (statute approach); Conceptual approach (conceptual approach); The case approach. In the case under investigation, ASN subordinates must accept and be convicted of committing a criminal act of participating as referred to in Article 55 of the Criminal Code. Therefore it is very important for ASNs to know and understand the steps, and what legal or non-legal remedies can be taken by subordinate ASNs to avoid criminal proceedings and the impact of criminal acts that they will experience. When an ASN feels or can predict that the order of their superior has the potential to become a corruption law problem, the ASN should have the courage to refuse the order of their superior so that the ASN is not burdened with responsibility for dealing with criminal corruption that has occurred. It is better for ASN to conduct legal consultations with competent parties before carrying out orders from superiors that have the potential to become criminal law problems for corruption. Keywords: ASN, Special Crimes, Corruption, Article 55 of the Criminal Code (participating)